Identifying Neuropeptide and G Protein-Coupled Receptors of Juvenile Oriental River Prawn (Macrobrachium nipponense) in Response to Salinity Acclimation - Sun, Shengming; Zhu, Mengru; Pan, Fangyan; Feng, Jianbin; Li, Jiale (Frontiers in Endocrinology, 2020)
Neuropeptides and their G protein-coupled receptors (GPCRs) from the central nervous system regulate the physiological responses of crustaceans. However in crustaceans, our knowledge regarding GPCR expression patterns and phylogeny is limited. Thus, the present study aimed to analyze the eyestalk transcriptome of the oriental river prawn Macrobrachium nipponense in response to salinity acclimation. We obtained 162,250 unigenes after de novo assembly, and 1,392 and 1,409 differentially expressed genes were identified in the eyestalk of prawns in response to low and high salinity, respectively. We used combinatorial bioinformatic analyses to identify M. nipponense genes encoding GPCRs and neuropeptides. The mRNA levels of seven neuropeptides and one GPCR were validated in prawns in response to salinity acclimation using quantitative real-time reverse transcription polymerase chain reaction. A total of 148 GPCR-encoding transcripts belonging to three classes were identified, including 77 encoding GPCR-A proteins, 52 encoding GPCR-B proteins, and 19 encoding other GPCRs. The results increase our understanding of molecular basis of neural signaling in M. nipponense, which will promote further research into salinity acclimation of this crustacean.